2018
DOI: 10.1002/eat.22823
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the clinical outcomes of adolescents and young adults with broad autism spectrum traits and autism spectrum disorder and anorexia nervosa: A multi centre study

Abstract: Adolescents with AN and ASD traits show similar reductions in their eating disorder symptoms. Nevertheless, their social difficulties remain high suggesting that these are life-long difficulties rather than starvation effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 21 publications
7
54
0
Order By: Relevance
“…Understanding the commonalities which link autism and anorexia nervosa seems imperative, given that autistic individuals and those with high autistic traits seem disproportionately over-represented in populations with this deadly disorder [5, 7, 17-20, 38-41, 43, 45, 48, 49, 55, 91] and seem to tend towards a poorer prognosis and treatment response [7][8][9][10][11]55]. We scrutinized the relationship between autistic traits and eating psychopathology with a focus on one putative mediating factor that might hypothetically serve as a risk factor for ED in autistic people and those with high autistic traits: levels of alexithymia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding the commonalities which link autism and anorexia nervosa seems imperative, given that autistic individuals and those with high autistic traits seem disproportionately over-represented in populations with this deadly disorder [5, 7, 17-20, 38-41, 43, 45, 48, 49, 55, 91] and seem to tend towards a poorer prognosis and treatment response [7][8][9][10][11]55]. We scrutinized the relationship between autistic traits and eating psychopathology with a focus on one putative mediating factor that might hypothetically serve as a risk factor for ED in autistic people and those with high autistic traits: levels of alexithymia.…”
Section: Discussionmentioning
confidence: 99%
“…A well-documented but poorly understood relationship exists between autism spectrum conditions (ASC) and anorexia nervosa (AN), conditions both associated with long-term morbidity and increased mortality [1][2][3][4]. The health risks associated with both conditions paint a worrying picture for the disproportionate number of autistic individuals found amongst those suffering from AN [5][6][7], as does the fact that autism and autistic traits seem to be associated with poorer prognosis and treatment response [7][8][9][10][11]. It is crucial to understand the mechanisms which may explain the heightened cooccurrence of these conditions and offer important insights to treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these traits can become exacerbated by the starvation of the acute illness (Treasure, ) and add to the complexity of the illness. It is unclear whether these traits adversely affect outcome (Nazar et al, ) and whether treatment should be adjusted to cater for the specific needs of these individuals. Starvation produces autistic‐like features, exacerbating obsessive–compulsive traits, and reducing social cognition.…”
Section: Clinical Practice and Summarymentioning
confidence: 99%
“…It has been suggested that high levels of ASD traits found in a proportion of those with AN may be due to the effects of starvation, and do not represent true ASD (26). However, several studies have found that body mass index (BMI), which is often used as a measure of illness severity, is not associated with ASD traits in individuals with AN (27)(28)(29)(30)(31)(32)(33). A few of these studies also examined associations with illness duration, finding that those with high ASD traits had not been ill for a significantly longer period of time than those with low ASD traits (29,33).…”
Section: Introductionmentioning
confidence: 99%